Východiska soužití: Romové v názoru žáků 8. tříd české základní školy - Moravcová, Mirjam (Lidé města, 2000)
The paper analyzes the look of a selected group of the Czech youth at Romany fellow citizens. lt is based on the data from research of xenophobia and subconscious racism conducted among the pupils of the 8th classes of Czech elementary schools by means of a questionnaire survey. The survey, carried aut at the initiative of the Czech Ministry of Education and Youth in May and June 1998, ascertained the views in 25 selected towns of Bohemia, Moravia and Silesia in the contemporary situation of a starting voluntary emigration of Romany groups from the Czech Republic (see Annex, Tables I to VIII). A broadly conceived sample of questions also included this question: ''For what do you admire Romanies?" (and of course for what do your admire Americans, Czechs, Swedes and the Vietnamese?). Replies were given by 3,438 pupils. An analysis of replies to this single question examines the views of 13 to 14-year-old schoolchildren about Romanies. The localities of research basically covered the area of the Czech Republic as evidenced by the results of the conducted ethnographic research (see Map 1). The basically inspiring question "For what do you admire Romanies?" deliberately prompted a search for positive features of Romany fellow citizens. The fact that the opposite question "Why do you mind Romanies?" was not asked was due to the rightful reservations by headteachers. Nevertheless, even the positively formulaled question also provided the children with an opportunity of voicing not only obliging, but also reserved, rejecting and xenophobic positions. In these cases the children used expediently and without any hindrance hyperboles, jokes and sarcasm. The asked children reacted to the question "For what do you admire Romanies?" in six various ways: (1) By ignoring the question. (2) Helplessly. (3) By rejecting the question. (4) By formulating cultural and social phenomena, facts and interactions for which Romanies can or cannot be admired. (5) By rejecting the opportunity of voicing any admiration for Romanies; and (6) by voicing absolute sympathies ar antipathies (see Annex, Table II). The frequency of this or that reaction reflected the basic attitude of the children under observation in general-a rejecting, positive, or indifferent attitude. The ratio between the rejection of the question, declaration of equality, formulation of cultural distinctiveness and negation of admiration indicated in itself a considerable degree of vagueness, and lack of knowledge and the fact that this may be a taboo subject (see Chart 1). Ignorance of the question (29.4 %) and refusal of any possible admiration for Romanies (39.2 %) proved the decisive positions. However, the position of intolerance expressed by verbally declared intolerance (insults, personal attacks, calls for isolation or liquidation) was only voiced by 2.6 % of the children (see Table 10). An equally small group of children advocated the position of cultural equality (2.4 %), expressing their unreserved admiration for Romanies without any further explanation (0.4 %) (see Tables 2, 11). Real facts, for which Romanies can be admired or, on the other hand, criticized, were presented by only 19.4 % of the children under observation, who have thus complied with the task of properly filling in the questionnaire. These children noticed six elements of Romanies' presence in the Czech Republic: (1) The patterns of behavior and persona! qualities they regard as typical of Romanies from their point or view. (2) The Romanies' culture and life style. (3) Internal links of Romany society. (4) The Romanies' physical appearance; (5) The position of Romany population in the Czech Republic; and finally (6) the Romanies' attitude to the civic society of the country which has become their homeland (see Chart 2, Tables 3-9). The analysis evaluated the ascertained positions of children distinguishing the position of boys and girls. It also asked the question about the links between the adopted positions and the children's family background in terms of ethnic and social signs and the question of local circumstances and conditioning of certain attitudes (see Annex, Tables I, III-VII). The analysis of answers from the pupils of 8th classes of Czech elementary schools in 25 towns in Bohemia, Moravia and Silesia to the question For what do you admire Romanies? has brought the following findings valid for the places in which the survey was carried aut. (1) The presence of Romanies in the Czech Republic is perceived by schoolchildren aged 13 to 14 as something natural. (2) The building of children's attitude to Romanies is not a general affair. For the time being, the relationship has been created by means of a transfer of cultural and ethnic stereotypes inside a family rather than through generally spread positions. Moreover, there was found no apparent underlying dependence on the social and professional orientation and the educational level of the father of the family. Perhaps only the social environment of parents with higher education significantly unites the children's position. On the one hand, it leads to positive perception of the Romanies' culture, but il also leaves more space for the influence of intolerant atmosphere. (3) The ideology of extremist groups has influenced a part of the youth, but only a very small portion. By contrast, the highest numerical representation appears in the group of those who have resisted the pressure and declared the position of cultural equality. (4) Those children who explained their admiration for Romanies with facts from their day-to-clay life mostly found positive things. (5) In the generational group of children of older school age the deeply rooted stereotypes of a Romany are being transformed. The picture of the Romany as a dishonest man and parasite is giving way to the picture of a victim. (6) ln general, the children's attitudes differed depending on their place of residence or the towns in which they live. Children from the towns of northeast Moravia, Děčín and Česká Kamenice tended to assume the position of voicing no view on inter-ethnic, which actually meant Czech-Romany, relations. Children from most east Bohemian towns, Český Krumlov and Nový Jičín displayed tolerance and accommodating approach to the Czech-Romany dialogue. By contrast, children from Litoměřice, Sokolov, Kutná Hora, Choceň and some districts of Prague and Brno tended to display a higher degree of intolerance. (7) A higher tendency toward intolerance provokes in some places opposite tendencies toward tolerance, apparently as part of an unguided process. In this clash one can see the emergence of three models of children' local reaction to intolerance of Romanies: an attitude accepting intolerance, an indifferent attitude, and an intensively defensive attitude. (8) Programs of education for ethnic tolerance, launched within a school or locality (the Prague 10 district, Český Krumlov, Nový Jičín) mainly influence among the children the ability to perceive the Romanies' cultural distinctiveness. (9) The 13 to 14-year-old children are building their attitude to Romanies on three positions: a. on the position of cultural relativism and humanism; b. on the position of conscious ethno-centrism (of various quality); and c. on the position of indifference. (10) The occurrence of children who said that it is impossible to admire Romanies for anything and who voiced their basic reservation (statements such as I don't like them), prompts a serious reflection from the viewpoint of positive dialogue. This highlights the degree of ignorance, lack of interest, indifference and contempt. The intensity of these attitudes to Romany fellow citizens, the attitudes which are basically blocking any positive approach, also transpired from a comparison of these attitudes voiced for Americans, Czechs, Swedes and Vietnamese (see Chart 3). One can evaluate as socially most dangerous not aggressive ethno-centrism, which was adopted by a relatively small group of children, but a tendency toward indifference and separation inside one's own ethnic group. This creates conditions for the emergence of opaque barriers to a positive dialogue and mutual opening of individua! ethnic communities living in the Czech Republic. However, it should be stressed that the signs of isolationism in relation to Romanies within the Czech civic society were displayed in a higher degree by children from other than Czech or Slovak families (most notably inside the Vietnamese families).